(untitled) (Journal of the College of Basic Education, 2025)
In 1914, Iraq was subjected to a British occupation that was carefully planned and executed in stages, with the goal of controlling the country’s resources. Similarly, in 2003, Iraq experienced another occupation, this time by the United States, which was also meticulously planned. The objective of the American occupation closely resembled that of the British—establishing control over Iraq’s resources The British justified their occupation by claiming they were rescuing Iraq from Ottoman rule, while the Americans justified theirs as a mission to liberate Iraq from the dictatorship of Saddam Hussein. Both occupations relied on military force and had similarities in governing Iraq after military operations ended. However, they differed in their administrative approaches. The British initially formed a temporary government consisting of Iraqi figures, whereas the Americans established a Governing Council composed of Iraqi figures who had been living abroad The British favored a hereditary monarchy and selected an Arab king through a public referendum held in Iraq, forming a government to administer the country. In contrast, the Americans preferred a republican system, with the president and government chosen through a constituent assembly The British signed a treaty with the Iraqi government to secure their interests and maintain their influence. A constituent assembly was then convened to ratify the treaty, draft a constitution, and establish a law for the parliament. On the other hand, the Americans postponed treaty negotiations until Iraq’s constitutional institutions were fully established, including the drafting of a constitution, the formation of a parliament, and the emergence of a permanent government. Only after these steps were completed did the United States sign a treaty with Iraq. Ultimately, both occupiers reached a similar outcome: securing their ability to impose their interests on Iraq